Studies of run-away electron beams and hard x-ray emission in ISTTOK tokamak - Jakubowski, L.; Plyusnin, V.V.; Malinowski, K.; Sadowski, M.J.; Zebrowski, J.; Rabinski, M.; Fernandes, H.; Silva, C.; Duarte, P.; Jakubowski, M. (Вопросы атомной науки и техники, 2011)
The paper describes measurements of fast run-away electron beams emitted from a plasma torus in the ISTTOK tokamak, which were performed by means of a new Cherenkov-type detector equipped with four radiators made of aluminium-nitrate (AlN) crystals of 10 mm in diameter and 2.5 mm in thickness each. The measuring head was fixed to a movable support, which enabled the radiators to be placed in chosen positions along the minor radius of ISTTOK. The radiators were coated with molybdenum (Mo) layers of different thicknesses since the main aim of this study was to estimate an energy spectrum of the recorded electrons. Attention was also paid to measurements of hard X-rays emitted from ISTTOK and to their correlations with run-away electrons. The investigated correlations showed that the both emissions are strongly coupled.